Consumo de Emerita analoga “muy muy” y su infección por larvas Profilicollis altmani en las playas del sur de lima - 2010. - Rojas Meza y Cols., Victor Jorge (2019)
This study determines the incidence of infection with Profilicollis altmani in 2,300 specimens of Emerita analoga or “muy muy", and its consumption by people living in near the South beaches of Peru, from the Costa Verde until the province of Cañete, during the months of october through december 2010.Collected crustaceans, 1,792 (77,91%) were infected. To see the larvae of Profilicollis altmani they proceeded to dissect by extracting the shell of the "muy muy" leaving exposed the hemocelomatica cavity founding 3,979, with an abundance average total of 1, 73 (1-22) with larvae of acanthocephala in cistacantos State such as Profilicollis altmani. From the 500 people surveyed, the 25, 8% consumed "muy muy" in their food. 25, 8% that consumed "muy muy", 3,04% consumed in “Ceviche”, 12,4% in omelets and 10% consumed in other forms. So, we can conclude that the "muy muy" from the South beaches in Lima are highly infected with Profilicollis altmani, which may be a health Public problem.